Solution-Grown Zn/Al Layered Double Hydroxide Nanoplatelets onto Al Thin Films: Fine Control of Position and Lateral Thickness. (27th April 2015) - Scarpellini, D.; Leonardi, C.; Mattoccia, A.; Di Giamberardino, L.; Medaglia, P. G.; Mantini, G.; Gatta, F.; Giovine, E.; Foglietti, V.; Falconi, C.; Orsini, A.; Pizzoferrato, R.
Abstract : We have grown nanostructured films of Zn/Al Layered Double Hydroxide (LDH) on different substrates by combining the deposition of an aluminum micropatterned thin layer with a successive one-step room-temperature wet-chemistry process. The resulting LDH film is made of lamellar-like nanoplatelets mainly oriented perpendicular to the substrate. Since the aluminum layer acts as both reactant and seed for the synthesis of the LDH, the growth can be easily confined with submicrometric-level resolution (about ±0.5 μ m) by prepatterning the aluminum layer with conventional photolithographic techniques. Moreover, we demonstrate real-time monitoring of the LDH growth process by simply measuring the resistance of the residual aluminum film. If the aluminum layer is thinner than 250 nm, the morphology of LDH nanoplatelets is less regular and their final thickness linearly depends on the initial amount of aluminum. This peculiarity allows accurately controlling the LDH nanoplatelet thickness (with uncertainty of about ±10%) by varying the thickness of the predeposited aluminum film. Since the proposed growth procedure is fully compatible with MEMS/CMOS technology, our results may be useful for the fabrication of micro-/nanodevices.